My social media for seniors - Miller, Michael (Hoboken, New Jersey, USA Que, 2020)
"Learn how to get the most out of social media! We've identified the essential skills you need to stay connected with the people you care about; reconnect with old friends and classmates; and share your life with loved ones near and far. Our crystal-clear instructions respect your smarts but never assume you're an expert. Big, colorful photos on nearly every page make this book incredibly easy to read and use!"--
What social media are--and why we use them -- Separating fact from fiction online -- What to share--and what not to share--on social media -- Using social media--safely and privately -- Comparing the most popular social media -- Keeping in touch with friends and family on Facebook -- Sharing pictures and videos on Facebook -- Discovering interesting groups on Facebook -- Configuring Facebook's privacy settings -- Following interesting people on Twitter -- Tweeting and retweeting on Twitter -- Pinning and repinning on Pinterest -- Finding other users and boards to follow on Pinterest -- Fine-tuning your professional profile on LinkedIn -- Connecting with people and businesses on LinkedIn -- Sharing photos with Instagram -- Getting social on message boards and comments sections -- Getting social with video chats -- Using social media to find old friends -- Exploring other social media.
"AARP real possibilities."
quepublishing.com
"Covers Facebook, Instagram, LinkedIn, Pinterest, and Twitter"--Cover.
Includes index.
108914
Keywords: Social media; Computers and older people; Computers and the elderly; Technology and the elderly; Instructional and educational works